Co-creating mental health promotion and prevention interventions with groups in vulnerable situations in Europe: a mixed-methods study protocol for co-creation implementation and participatory evaluation - Teixeira, Raquel; de Freitas, Cláudia; Sanna, Liuska; Prina, Eleonora; Turrini, Giulia; Brizar, Amber S.; Gherdan, Cătălin; Kazlauskas, Evaldas; Dumarkaitė, Austėja; Wasmus, Henrik; Fleck, Leonie; Reininghaus, Ulrich; et al. (BioMed Central, 2026)
Background
Co-creation has emerged as a crucial strategy for addressing complex public health challenges, including promotion and prevention of mental health concerns. While the evidence base for effective interventions continues to grow, significant gaps remain in their implementation and integration into real-world settings. Co-creation offers a valuable tool for strengthening mental health promotion strategies, ensuring that interventions are evidence-based, contextually relevant, culturally sensitive, sustainable and acceptable to those directly affected. However, there is a paucity of studies examining the evaluation of co-creation research, particularly regarding how participatory methods foster adaptation and influence outcomes and long-term sustainability. This protocol outlines a study designed to implement, evaluate and strengthen co-creation methodologies through a participatory and formative evaluation approach.
Methods
This study adopts a mixed-methods design within the ADVANCE project, a multi-country initiative focused on co-creating mental health promotion and prevention interventions with groups in vulnerable situations across seven European countries. End-users, healthcare professionals, and decision-makers will be engaged throughout the project in both intervention design and evaluation. Co-creation activities initiated with intervention scenario building and prioritization, drawing on desk reviews and online Delphi surveys co-developed with locally-set Society Advisory Groups (SAGs). The selection of intervention scenarios for implementation was performed using scenario-based workshops involving stakeholders in six partner countries. A second goal is to evaluate the co-creation process, which was co-designed in consultation with country teams and SAGs. A longitudinal qualitative study based on semistructured interviews with co-creators across two time points will be conducted, following the co-development of the interview guide through an online World Café.
Discussion
This study introduces an innovative approach by embedding participatory and formative evaluation into the co-creation process, enabling ongoing adaptation of co-creation activities. Through continuous stakeholder engagement, the project seeks to address barriers deriving from power imbalances, conflicting priorities, and resource limitations. Qualitative and participatory methods will be combined to elicit stakeholders’ views, identify drawbacks and promote adjustments to ensure meaningful collaboration and reduce participation fatigue. Expected outcomes include actionable recommendations to inform policy, reduce stigma and foster the co-creation of more inclusive, effective, sustainable and scalable mental health promotion and prevention strategies across Europe.